2021
DOI: 10.1016/j.ajur.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epigenetic pathogenesis of germ cell tumors

Abstract: The development of germ cell tumors (GCTs) is a unique pathogenesis occurring at an early developmental stage during specification, migration or colonization of primordial germ cells (PGCs) in the genital ridge. Since driver mutations could not be identified so far, the involvement of the epigenetic machinery during the pathogenesis seems to play a crucial role. Currently, it is investigated whether epigenetic modifications occurring between the omnipotent two-cell stage and the pluripotent implanting PGCs mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 77 publications
(142 reference statements)
1
22
0
Order By: Relevance
“…Since TRIM71 is known to regulate proliferation in several cell lines ( Chen et al, 2013 ; Ren et al, 2018 ; Hu et al, 2019 ; Torres-Fernández et al, 2019 ), we next wanted to investigate whether TRIM71 may control proliferation also in PGCs. Because the isolation of sufficient PGCs from genital ridges for its absolute reliable quantification is technically very challenging, we used the human GCT-derived seminoma cell line TCam-2, which is a widely accepted in vitro PGC model ( Irie et al, 2015 ; Sugawa et al, 2015 ; Nettersheim et al, 2016a , b , c ; Mitsunaga et al, 2017 ; Müller et al, 2020 ) and expresses high TRIM71 levels, similar to other GCT-derived cell lines ( Supplementary Figure 8A ). To this end, we knocked down (KD) TRIM71 with two different siRNAs ( Figure 4A ), and monitored the increase in cell numbers over time ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since TRIM71 is known to regulate proliferation in several cell lines ( Chen et al, 2013 ; Ren et al, 2018 ; Hu et al, 2019 ; Torres-Fernández et al, 2019 ), we next wanted to investigate whether TRIM71 may control proliferation also in PGCs. Because the isolation of sufficient PGCs from genital ridges for its absolute reliable quantification is technically very challenging, we used the human GCT-derived seminoma cell line TCam-2, which is a widely accepted in vitro PGC model ( Irie et al, 2015 ; Sugawa et al, 2015 ; Nettersheim et al, 2016a , b , c ; Mitsunaga et al, 2017 ; Müller et al, 2020 ) and expresses high TRIM71 levels, similar to other GCT-derived cell lines ( Supplementary Figure 8A ). To this end, we knocked down (KD) TRIM71 with two different siRNAs ( Figure 4A ), and monitored the increase in cell numbers over time ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…While we excluded in vivo PGC migration defects upon TRIM71 depletion, in vitro proliferation assays with TCam-2 and NCCIT cells showed that TRIM71 actively promotes proliferation of these GCT-derived cell lines. Given the similarities of TCam-2 cells -and to a lesser extent of NCCIT cells -with PGCs (Irie et al, 2015;Sugawa et al, 2015;Nettersheim et al, 2016a,b,c;Mitsunaga et al, 2017;Müller et al, 2020), our results suggest that TRIM71 may be involved in the control of PGC proliferation after they reach the genital ridges, when a significant expansion of the PGC pool occurs (Tam and Snow, 1981;Anderson et al, 2000;Bowles and Koopman, 2010;Ewen and Koopman, 2010). To strengthen this notion, future experiments should investigate the role of TRIM71 in the proliferation of post-migratory PGCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Female germ cell tumors may be derived from various types of cells including surface epithelium, stroma, or follicular cell elements. Ovarian germ cell tumors (OGCTs) are mostly associated with early developmental stages of primitive germ cells of the embryonic gonad and are developed during specification, migration, and colonization of the primordial germ cells in the genital ridges [ 79 , 80 ].…”
Section: Germ Cell Tumor Development and Their Molecular Regulatiomentioning
confidence: 99%
“…Compared to most other cancer types, GCTs harbor a very low mutational burden [ 7 , 8 ]. Hence, it is postulated that epigenetic aberrations could be the driver of tumorigenesis in GCTs [ 3 , 9 ]. It has been shown that the GCT subtypes vary greatly in their DNA methylation status, i.e.…”
Section: Introductionmentioning
confidence: 99%